Creation and shaping of the global solar photovoltaic (PV) market - Valtteri Kaartemo (Emerald, 2022)
Purpose: This chapter seeks to place Paris agreement on anthropogenic greenhouse gases (COP21) in a wider picture on how the global solar photovoltaic (PV) market has been created and shaped over decades. The chapter discusses the role of solar PV actors, as well as other actors in market shaping process. The aim is to show how the COP21 can be interpreted in a longer historical perspective. Approach: The book chapter builds on expert interviews conducted after the COP21, as well as secondary data on historical studies on evolution of solar energy markets in various countries. Findings: Although scientists and entrepreneurs have been important in creating and shaping the global solar PV market, it is noted that also other actors have had influence on the market development. Particularly, politicians are seen as having crucial role through legislation and funding. Unfortunate to solar PV market, support has fluctuated over time. The COP21 provides a clear pathway for positive support, and it is expected to bind governments for pro-solar politics even during low prices of fossil fuels and economic downturn. Practical implications: The chapter provides an overview of what has happened in the history of global solar PV market. It gives reasoning why the COP21 is important in securing support to solar PV market. Thus, it can provide reasoning why the COP21 can make difference. Originality/value: This is the first academic study that portrays the COP21 against historical evolution of global solar PV market.
Climate Change and the 2030 Corporate Agenda for Sustainable Development